2005
DOI: 10.1002/cncr.21070
|View full text |Cite
|
Sign up to set email alerts
|

Women age ≤ 35 years with primary breast carcinoma

Abstract: BACKGROUNDThe purpose of the current study was to describe a population of young patients with breast carcinoma, their characteristics at the time of diagnosis, and the association of these characteristics with disease recurrence and survival.METHODSFour hundred fifty‐two women age ≤ 35 years with breast carcinoma were registered at The University of Texas M. D. Anderson Cancer Center (Houston, TX) between 1990 and 2002. The relation between clinicopathologic factors and disease recurrence‐free survival (RFS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
31
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 24 publications
7
31
2
5
Order By: Relevance
“…These results are substantiated by a recent study from investigators at the MD Anderson Cancer Center, showing that among very young breast cancer patients (p35 years), a family history of ovarian cancer strongly impaired disease-free and overall survival (Gonzalez-Angulo et al, 2005). Nevertheless, the low number of cases prevented us from drawing definite conclusions and the results should be used only to generate hypotheses.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These results are substantiated by a recent study from investigators at the MD Anderson Cancer Center, showing that among very young breast cancer patients (p35 years), a family history of ovarian cancer strongly impaired disease-free and overall survival (Gonzalez-Angulo et al, 2005). Nevertheless, the low number of cases prevented us from drawing definite conclusions and the results should be used only to generate hypotheses.…”
Section: Discussionmentioning
confidence: 61%
“…Some studies have shown improved survival rates among breast cancer patients with affected relatives compared to those without a family history (Malone et al, 1996;Mohammed et al, 1998), some reported poorer survival rates (Slattery et al, 1993;Gonzalez-Angulo et al, 2005), and others did not find any survival difference between patients with or without a family history (Greenberg et al, 1985;Kinoshita et al, 2004). Although most of these studies used multivariate analysis to adjust mortality risks for other prognostic variables, none of them adjusted for use of systemic therapy.…”
mentioning
confidence: 99%
“…Given the delayed diagnosis, ~75% of these cancer cases are diagnosed at an advanced stage, with 50-80% lymph node involvement and higher SBR grading (40% SBR 2 and 50% SBR 3). Hormone receptors are less likely to be positive (68% of those <40 years of age vs. 80% of ≥40 years), and HER2 is more frequently over expressed in younger patients than in postmenopausal females (19,20). Triple-negative tumors (negative for ER, PR and HER2) are more common in younger patients (21).…”
Section: Discussionmentioning
confidence: 99%
“…recurrence. Some studies have shown improved survival rates among breast cancer patients with affected relatives compared to those without an FH [9,10], some reported poorer survival rates [11], and others did not find any survival difference between patients with or without an FH [12,13]. Most of these studies are case-control studies with relatively small numbers of patients with no long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%